Genetic Mapping of the Incompatibility Locus in Olive and Development of a Linked Sequence-Tagged Site Marker - Mariotti, Roberto; Fornasiero, Alice; Mousavi, Soraya; Cultrera, Nicolò G.M.; Brizioli, Federico; Pandolfi, Saverio; Passeri, Valentina; Rossi, Martina; Magris, Gabriele; Scalabrin, Simone; Scaglione, Davide; Di Gaspero, Gabriele; et al. (Frontiers in Plant Science, 2020)
The genetic control of self-incompatibility (SI) has been recently disclosed in olive. Inter-varietal crossing confirmed the presence of only two incompatibility groups (G1 and G2), suggesting a simple Mendelian inheritance of the trait. A double digest restriction associated DNA (ddRAD) sequencing of a biparental population segregating for incompatibility groups has been performed and high-density linkage maps were constructed in order to map the SI locus and identify gene candidates and linked markers. The progeny consisted of a full-sib family of 229 individuals derived from the cross ‘Leccino’ (G1) × ‘Dolce Agogia’ (G2) varieties, segregating 1:1 (G1:G2), in accordance with a diallelic self-incompatibility (DSI) model. A total of 16,743 single nucleotide polymorphisms was identified, 7,006 in the female parent ‘Leccino’ and 9,737 in the male parent ‘Dolce Agogia.’ Each parental map consisted of 23 linkage groups and showed an unusual large size (5,680 cM in ‘Leccino’ and 3,538 cM in ‘Dolce Agogia’). Recombination was decreased across all linkage groups in pollen mother cells of ‘Dolce Agogia,’ the parent with higher heterozygosity, compared to megaspore mother cells of ‘Leccino,’ in a context of a species that showed exceptionally high recombination rates. A subset of 109 adult plants was assigned to either incompatibility group by a stigma test and the diallelic self-incompatibility (DSI) locus was mapped to an interval of 5.4 cM on linkage group 18. This region spanned a size of approximately 300 Kb in the olive genome assembly. We developed a sequence-tagged site marker in the DSI locus and identified five haplotypes in 57 cultivars with known incompatibility group assignment. A combination of two single-nucleotide polymorphisms (SNPs) was sufficient to predict G1 or G2 phenotypes in olive cultivars, enabling early marker-assisted selection of compatible genotypes and allowing for a rapid screening of inter-compatibility among cultivars in order to guarantee effective fertilization and increase olive production. The construction of high-density linkage maps has led to the development of the first functional marker in olive and provided positional candidate genes in the SI locus.